Forensic Assessment of Genotoxic Effects of Lead Metal on leaf Phragmites australis Using Random Amplified Polymorphic DNA (RAPD-PCR) Markers - Ahmed Ghalib Ibraheem; Reyam Naji Ajmi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The influence lead metal on DNA integrity in leaf plant can measure by potential effects of pollutantsaccumulation metal, Pb in leaf plant Phragmites australis was subjected to RAPD analysis, have been foundmetal at concentrations of S1, S2,S3 (0.045 , 2.97, 0.93) Respectively. polymorphisms became evident asthe presence and absence of DNA fragments in affected samples compared to effect samples. Five primewas selected OP-L05, OP-M14, OP-M20, OP-V09 and OP-M05 were used , the genomic DNA of leaf didnot appear polymorphic band at OP-L05 except molecular weight 600bp and presence of polymorphic band,OP-M20 show only polymorphic band at 850bp,OP-M05 did not show any polymorphisms and OP-M14,OP-V09 primers appeared polymorphisms when compare unexposed in control, this study confirmed RAPDmarkers a fast and simple technique can be used detection of forensic environmental.